The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1073/pnas.1922344117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a ketogenic diet on hepatic steatosis and hepatic mitochondrial metabolism in nonalcoholic fatty liver disease

Abstract: Weight loss by ketogenic diet (KD) has gained popularity in management of nonalcoholic fatty liver disease (NAFLD). KD rapidly reverses NAFLD and insulin resistance despite increasing circulating nonesterified fatty acids (NEFA), the main substrate for synthesis of intrahepatic triglycerides (IHTG). To explore the underlying mechanism, we quantified hepatic mitochondrial fluxes and their regulators in humans by using positional isotopomer NMR tracer analysis. Ten overweight/obese subjects received stable isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(170 citation statements)
references
References 62 publications
(114 reference statements)
5
161
3
1
Order By: Relevance
“…Although one could argue that these results relate to the inequality in calorie intake between VLCKD and conventional LC diets, the differences regarding the correlation between VAT and PDFF at baseline and at 2 months between groups may indicate differently. Studies have shown that the fast reduction in liver fat is probably more related to the ketogenic state than to overall calorie restriction (17), and insulin resistance has been suggested as a key mechanism in this process (30). In a prior study, Luukkonen et al (17) have described a high rate of liver triglycerides hydrolysis during the increased hepatic production of ketones, as serum insulin concentrations, endogenous glucose production, and hepatic insulin resistance decrease in patients undergoing VLCKD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although one could argue that these results relate to the inequality in calorie intake between VLCKD and conventional LC diets, the differences regarding the correlation between VAT and PDFF at baseline and at 2 months between groups may indicate differently. Studies have shown that the fast reduction in liver fat is probably more related to the ketogenic state than to overall calorie restriction (17), and insulin resistance has been suggested as a key mechanism in this process (30). In a prior study, Luukkonen et al (17) have described a high rate of liver triglycerides hydrolysis during the increased hepatic production of ketones, as serum insulin concentrations, endogenous glucose production, and hepatic insulin resistance decrease in patients undergoing VLCKD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the fast reduction in liver fat is probably more related to the ketogenic state than to overall calorie restriction (17), and insulin resistance has been suggested as a key mechanism in this process (30). In a prior study, Luukkonen et al (17) have described a high rate of liver triglycerides hydrolysis during the increased hepatic production of ketones, as serum insulin concentrations, endogenous glucose production, and hepatic insulin resistance decrease in patients undergoing VLCKD. In our study, however, this relationship was not confirmed as differences in reduction of Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) between both groups failed to reach statistical differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several dietary intervention strategies have been tested: modification of diet composition (for example, Mediterranean, low-carbohydrate, low-fat, and ketogenic diets) or feeding behavior (time-restricted feeding or intermittent fasting) with the Mediterranean diet showing the most promising results for reducing hepatic steatosis, dyslipidemia, and other metabolic comorbidities (reviewed by Saeed et al) [ 119 ]. A recent study of overweight and obese patients showed that consumption of a ketogenic diet reduced intrahepatic fat content (measured by MRS) and markedly increased hepatic mitochondrial activity [ 120 ]. This was paralleled by a 25% reduction in plasma TG levels and improved insulin sensitivity despite minimal (∼3%) weight loss.…”
Section: Therapeutic Strategies and Their Potential Impact On Cvd Rismentioning
confidence: 99%